MODUL PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PRESTASI BELAJAR KOMPETENSI LAS OKSI ASETELIN PADA MAHASISWA PENDIDIKAN TEKNIK MESIN FAKULTAS TEKNIK UNIVERSITAS NEGERI SEMARANG - Suharmanto, Agus (Jurnal Penelitian Pendidikan, 2011)
The problem in this study were: whether the Interactive Learning Module can improve achievement and learning outcomes Oxygen acetylene Welding Course Education Student of Mechanical Engineering, State University of Semarang. The purpose of making this interactive learning module are: to determine whether student learning outcomes of Mechanical Engineering Education, State University of Semarang Lecture Oxygen acetylene welding can be increased with the Interactive Learning Module and find out whether the learning activities of Education Student of Mechanical Engineering Faculty of Engineering, State University of Semarang on Oxygen Welding courses acetylene can be improved with an interactive learning module. Subjects in the study of this class action are: Student Education Mechanical Engineering Faculty of Engineering, State University of Semarang Odd semester of 2011/2012 academic year, amounting to 40 students. The research method used in this study were: research methods class action (PTK). This class action research using research design adopted in the two cycles, namely cycle I and cycle II. The results of this study are: Interactive Learning Module can improve achievement and learning outcomes on Oxygen acetylene Welding Course Education Student of Mechanical Engineering, State University of Semarang, the Interactive Learning Module can improve achievement and learning outcomes in Las oxy Asetelin competence in education of students of Mechanical Engineering, Faculty of Engineering State University of Semarang.